Perlindungan Hukum Bagi Konsumen Dalam Transaksi Jual Beli Online (E-Commerce) di Indonesia - Novia Sartika; Ananda Fajar Subakhti; Ilham Kurniawan (Universitas Batanghari Jambi, 2026)
The rapid development of information technology has significantly accelerated the growth of electronic commerce (e-commerce) in Indonesia. Although e-commerce provides greater convenience in conducting commercial transactions, it also gives rise to various legal issues, including online fraud, breach of contract, misuse of personal data, and discrepancies between the goods or services received and the information provided by sellers. This study aims to analyze the legal framework for consumer protection in e-commerce transactions in Indonesia, examine the enforcement of laws against electronic commerce business operators, and identify the legal protection mechanisms available to users of electronic transactions. This research employs a normative juridical method using statutory and conceptual approaches. The legal materials consist of primary, secondary, and tertiary legal sources, which are analyzed qualitatively using a descriptive-analytical method. The findings indicate that consumer protection in e-commerce transactions is comprehensively regulated under Law Number 8 of 1999 on Consumer Protection, Law Number 1 of 2024 on Electronic Information and Transactions, along with various implementing regulations. Law enforcement against business actors is carried out through administrative, civil, and criminal legal mechanisms to ensure legal certainty, protect consumer rights, and establish a secure and trustworthy digital trading environment. Nevertheless, the effectiveness of legal protection continues to face several challenges, including the rapid advancement of technology, low levels of public legal literacy, inadequate regulatory oversight, and the complexity of enforcing laws against cross-border business actors.